Double Fano Resonances in S-Shaped Plasmonic Metasurfaces in Terahertz Region - Xu, Weihang; Chen, Lingling; Zhu, Fangming; Liu, Jianjun; Sui, Chuanshuai; Hong, Zhi (Frontiers in Physics, 2020)
We numerically and experimentally demonstrated double Fano resonances in a simple S-shaped plasmonic metasurface in the terahertz frequency range. Apart from the LC resonance and electric dipole (ED) resonance, two trapped modes are excited in two different types of asymmetric S-shaped structures in the frequency range 0.2–1.4 THz, which are mainly attributed to a magnetic dipole (MD) and an electric quadrupole (EQ). Thereafter, double Fano resonances (one Fano and one electromagnetically induced transparency (EIT) resonance) are achieved via the coupling of the two dark trapped modes and a broad bright ED at normal incidence of the metasurfaces. Furthermore, under oblique incidence, strong Fano responses can be observed; they are considerably enhanced in asymmetric structures, and even in a symmetric structure. The proposed S-shaped plasmonic metasurfaces are easy to fabricate and have potential applications in multi-wavelength optical switches, filters‚ and sensors.